DEVELOPMENT AND VALIDATION OF MOXIFLOXACIN DETERMINATION IN HUMAN PLASMA BY HPLC-UV METHOD - T. N. Komarov; Yu. V. Medvedev; I. E. Shohin; Yu. E. Boldina; A. A. Lvova; E. S. Melnikov; E. N. Fisher; R. V. Ivanov; R. J. Maksvitis (Разработка и регистрация лекарственных средств, 2019)
A new method for determination of moxifloxacin in human plasma using HPLC with UV-detection is described. The sample preparation was made by protein precipitation by 50% trifluoracetic acid solution. The method was validated in terms of selectivity, calibration curve, accuracy, precision, lower limit of quantification, carry-over and stability. The analytical range was 100-5000 ng/mL. Limit of determination was 31 ng/mL. Method could be applied to moxifloxacin determination in plasma for PK and BE studies.